Potentiometric Study of Rhenium(V) Complex Formation With Azathioprine And Ceftriaxone - Gouda, Gamal Abdelaziz Hussein; Ali, Gomaa A. M. (The Malaysian Analytical Sciences Society, UKM, 2017)
The behavior of complex formation of Re(V) metal ion with azathioprine (AZ) and ceftriaxone (CE) as medicinal drugs has been investigated potentiometrically in 0.3 M hydrochloric acid. The stability constant of the prepared complexes has been determined and calculated at various temperatures. The obtained results showed that Re(V)-AZ system showed the formation 1:2, 1:3 and 1:4 complexes, while Re(V)-CE showed only 1:1 and 1:2 complexes. The complex formation suggests a successive displacement of the chloride molecules from the coordination sphere of the central ion by the AZ ligand. In addition, the effect of temperature on the complexes formation of Re(V) with AZ and CE was investigated. The entropy and enthalpy changes showed a favorable and exothermic process, respectively. The kinetic parameters of the formation complex process were calculated and discussed.